Increasing the Legal Perspective of Protection and Management of the environment Through Persuasive Communication in the Tanjung Raja Village Community: Peningkatan Perspektif Hukum Perlindungan Dan Pengelolaan Lingkungan Hidup Melalui Komunikasi Persuasif Pada Masyarakat Desa Tanjung Raja - Hagi Julio Salas Hagi (Pengabdian Kepada Masyarakat Cendekia, 2023)
Indonesia is a country with abundant and valuable biodiversity and natural resources. However, besides that there are many things that can threaten environmental sustainability such as the impact of climate change and improper environmental management. Law number 32 of 2009 concerning the protection and management of the environment is the solution in dealing with and dealing with this threat. Tanjung Raja Village is a village that has abundant natural resources. As an effort to guarantee its sustainability, it requires management with a legal understanding that supports it so that the goals can be achieved properly. Dissemination of environmental protection laws with a persuasive communication approach was carried out to increase people's perspectives on environmental law. This counseling showed significant results. This is based on the findings of indicator data on the success of counseling which reached stage 4. This success was also encouraged by the existence of persuasive communication techniques carried out by the presenters, namely through association, integration and organization techniques.